2005
DOI: 10.1038/ja.2005.27
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Biosynthetic Genes and Enzymes of Isoprenoids Produced by Actinomycetes

Abstract: Most Streptomyces strains are equipped with only the 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway for the formation of isopentenyl diphosphate, a common precursor of isoprenoids. In addition to this pathway, some Streptomyces strains possess the mevalonate (MV) pathway via which isoprenoid antibiotics are produced. We have recently cloned and analyzed the MV pathway gene clusters and their flanking regions from terpentecin, BE-40644, and furaquinocin A producers. All these clusters contained genes coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 80 publications
1
49
0
Order By: Relevance
“…7 HOW IT STARTED I have been studying the enzymes and genes responsible for the biosyntheses of isoprenoids produced by actinomycetes. 8 Approxi-mately 6 years ago, I tried to clone a gene cluster participating in the biosynthesis of KS-505a (Figure 2), which is produced by Streptomyces argenteolus strain A-2 and has a unique cyclized tetraterpene moiety and an aromatic moiety derived from OSB. 9 Antibiotic biosynthetic genes cloned from actinomycetes are usually clustered in a genomic DNA region, 8 and OSB is synthesized by the MenF, -D and -C enzymes in the known MK biosynthetic pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 HOW IT STARTED I have been studying the enzymes and genes responsible for the biosyntheses of isoprenoids produced by actinomycetes. 8 Approxi-mately 6 years ago, I tried to clone a gene cluster participating in the biosynthesis of KS-505a (Figure 2), which is produced by Streptomyces argenteolus strain A-2 and has a unique cyclized tetraterpene moiety and an aromatic moiety derived from OSB. 9 Antibiotic biosynthetic genes cloned from actinomycetes are usually clustered in a genomic DNA region, 8 and OSB is synthesized by the MenF, -D and -C enzymes in the known MK biosynthetic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…8 Approxi-mately 6 years ago, I tried to clone a gene cluster participating in the biosynthesis of KS-505a (Figure 2), which is produced by Streptomyces argenteolus strain A-2 and has a unique cyclized tetraterpene moiety and an aromatic moiety derived from OSB. 9 Antibiotic biosynthetic genes cloned from actinomycetes are usually clustered in a genomic DNA region, 8 and OSB is synthesized by the MenF, -D and -C enzymes in the known MK biosynthetic pathway. 1,2 Therefore, I first tried to clone menF, -D and -C orthologs from the KS505a producer, as actinomycetes are known to synthesize MK and the length of the prenyl side chain of MK has been used for taxonomic studies of actinomycetes.…”
Section: Introductionmentioning
confidence: 99%
“…31) It has been reported that many terpene cyclases have broad substrate specificities, and that other classes of terpenes have been created in vitro. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] A combination of studies identifying enzymatic products biosynthesized from unusual substrates and the analysis of genome sequences should lead not only to the discovery of additional functions of these enzymes in the organism, but also to the identification of novel natural terpenoids that have functions in their producers.…”
Section: Identification Of Bifunctional Sesquarterpene/ Triterpene Cymentioning
confidence: 99%
“…1. Since a number of genes responsible for the biosynthesis of terpenoids form clusters in microbial genomes, 5) we searched for ts among the genes around the HepPP synthase gene (hepS and hepT), as well as a putative TC gene (sqhC), in the B. subtilis genome, but we were not able to find any candidate. 29) Hence, we investigated 2,514 gene-disrupted strains of B. subtilis, provided by the National BioResource Project (NIG, Japan) to isolate ts.…”
mentioning
confidence: 99%
See 1 more Smart Citation